2009
DOI: 10.1007/s00428-009-0754-6
|View full text |Cite
|
Sign up to set email alerts
|

Infant and perinatal pulmonary hypoplasia frequently associated with brainstem hypodevelopment

Abstract: Recent anatomo-pathological studies have revealed a frequent associated hypoplasia of both arcuate nucleus and lungs in stillbirths. The purpose of this study is to analyze the lung and brainstem development in sudden unexplained perinatal death and sudden infant death syndrome (SIDS). A total of 51 cases were investigated. A complete autopsy was performed in each case. Anatomo-pathologic examination of the central autonomic nervous system included an in-depth study on histological serial sections of the brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Importantly, in humans, hypoplasia of several brainstem nuclei affected in our ATF2 mutant mice, including the inferior olivary nuclei, the facial, the dorsal vagal and the hypoglossal nuclei have been reported in cases of intrauterine or neonatal sudden death as well as in sudden infant death syndrome [35]. Interestingly, cranial motoneuron nuclei hypo-development is frequently associated with pulmonary hypoplasia and aspiration pneumonia [35], [36]. It is therefore plausible that the brainstem malformation caused by ATF2 mutation leads to similar respiratory defects to those seen in some forms of human sudden death syndromes.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Importantly, in humans, hypoplasia of several brainstem nuclei affected in our ATF2 mutant mice, including the inferior olivary nuclei, the facial, the dorsal vagal and the hypoglossal nuclei have been reported in cases of intrauterine or neonatal sudden death as well as in sudden infant death syndrome [35]. Interestingly, cranial motoneuron nuclei hypo-development is frequently associated with pulmonary hypoplasia and aspiration pneumonia [35], [36]. It is therefore plausible that the brainstem malformation caused by ATF2 mutation leads to similar respiratory defects to those seen in some forms of human sudden death syndromes.…”
Section: Discussionmentioning
confidence: 90%
“…Cranial motoneurons innervate muscles controlling airway dimensions and exhibit an important rhythmic respiratory activity that is synchronous with the activity of respiratory neurons of the medulla during expiration and inspiration [34]. Importantly, in humans, hypoplasia of several brainstem nuclei affected in our ATF2 mutant mice, including the inferior olivary nuclei, the facial, the dorsal vagal and the hypoglossal nuclei have been reported in cases of intrauterine or neonatal sudden death as well as in sudden infant death syndrome [35]. Interestingly, cranial motoneuron nuclei hypo-development is frequently associated with pulmonary hypoplasia and aspiration pneumonia [35], [36].…”
Section: Discussionmentioning
confidence: 92%
“…Previously, we have reported a high incidence of lung hypoplasia in subjects who died of Sudden Intrauterine Unexplained Death Syndrome (SIUDS) and Sudden Infant Death Syndrome (SIDS) [21,22]. In the present study we aimed to investigate whether the lung hypodevelopment frequently observed in these victims may be due, as shown in experimental studies, to a specific hyperactivation of the α7 nAChR subunit in cases of nicotine absorption in pregnancy.…”
Section: Introductionmentioning
confidence: 92%